Marulić's Love Poetry in Scotland - Novaković, Darko (1999)
Of the 141 poems contained in the codex Hunter 334 only eight were previously known; the remaining 600 verses are a new discovery. Surely the most challenging are the verses which present Marulić for the first time as a love poet.
Projekt MZOS
ENG